SCIENTIFIC PRECEDING OF STEERING MOTIVATION PERSONNEL TO ENERGY SAVINGS FOR BUILDING ENTERPRISES - Klimchuk , M.M. (The actual problems of regional economy development, 2017)
The article attempts to theoretical reconstruction of personnel motivation as a structural component of the economic process of energy saving management at the construction company. Interpretation of motivation as a multidimensional, whole involves the synergy of the development of some economic facets in relation to others, taking into account the characteristics of the subject and the object of motivation. The symbiosis of psychological and economic approaches in the process of studying the motivation of personnel for energy saving has given an opportunity to propose postulates: situational, mnemonic, spatial-temporal, and imaginative, representative.